The Influence of Transparency in Human Resource Development and Accountability on the Performance of PDAM Tirtabina Labuhanbatu Employees - Ahmad Akbar Nazrullah Siregar; Yuniman Zebua; Fadzil Hanafi Asnora (International Journal of Science, Technology & Management, 2026)
The Regional Drinking Water Company (PDAM) as a Regionally Owned Enterprise has a strategic role in providing clean water services to the community, so that improving employee performance is an important factor in supporting service quality. This study aims to analyze the effect of transparency in human resource development and accountability on employee performance at PDAM Tirtabina Labuhanbatu, both partially and simultaneously. The study used an associative quantitative approach with a saturated sampling technique on 74 employees. Data were collected through a Likert scale questionnaire and analyzed using multiple linear regression with t-test, F-test, and coefficient of determination (R²). The results showed that transparency in human resource development had a positive and significant effect on employee performance (t = 2.728; sig. = 0.008). Meanwhile, accountability did not have a significant effect on employee performance (t = 0.808; sig. = 0.422). Simultaneously, transparency in human resource development and accountability had a significant effect on employee performance (F = 4.182; sig. = 0.019). The coefficient of determination indicates that the two independent variables are able to explain employee performance by 50.5% (R² = 0.505), while the remainder is influenced by other factors outside the research model. This study recommends increasing transparency in HR development policies and strengthening a more measurable accountability system to encourage improved PDAM employee performance.